Clinical utility of exome sequencing in a pediatric epilepsy cohort. Issue 4 (21st February 2023) - Graifman, Jordana L.; Lippa, Natalie C.; Mulhern, Maureen S.; Bergner, Amanda L.; Sands, Tristan T.
Abstract: Objective: Exome sequencing (ES) has played an important role in the identification of causative variants for individuals with epilepsy and has proven to be a valuable diagnostic tool. Less is known about its clinical utility once a diagnosis is received. This study systematically reviewed the impact of ES results on clinical decision‐making and patient care in a pediatric epilepsy cohort at a tertiary care medical center. Methods: Pediatric patients with unexplained epilepsy were referred by their neurologist, and informed consent was obtained through an institutional review board–approved research ES protocol. For patients who received a genetic diagnosis, a retrospective chart review was completed of the probands and their relatives' medical records prior to and after genetic diagnosis. The following outcomes were explored: provider management recommendations, changes in care actually implemented, and anticipatory guidance provided regarding the proband's condition. Results: Fifty‐three probands met the inclusion criteria. Genetic diagnosis led to at least one provider recommendation in 41.5% families (22/53). Recommendations were observed in the following categories: medication, screening for non‐neurological comorbidities/referrals to specialists, referrals to clinical research/trials, and cascade testing. Anticipatory guidance including information about molecular diagnosis, prognosis, and relevant foundations/advocacy groups was also observed. Significance: Results demonstrate the clinical utility of ES for individuals with epilepsy across multiple aspects of patient care, including anti‐seizure medication (ASM) selection; screening for non‐neurological comorbidities and referrals to appropriate medical specialists; referral to reproductive genetic counseling; and access to research, information, and support resources. To our knowledge, this is the first study to evaluate the clinical utility of ES for a pediatric epilepsy cohort with broad epilepsy phenotypes. This work supports the implementation of ES as part of clinical care in this population.